Autobiographical self-translation – translator as the author, narrator and protagonist. (3rd April 2019) - Takahashi, Tomoko
ABSTRACT: In this article, I examine the process of autobiographical self-translation from narratological perspectives, using examples from the self-translation process I experienced translating my autobiography from Japanese into English. The main question asked is: What is the self-translation process like when the translator is also the author, narrator and protagonist? Self-translation is a complex process, and it becomes even more so, as in my case, when the author-translator serves as a historian, family biographer, autobiographer and nostalgic storyteller. Although the narrator remains constant throughout the story, her role, tone and persona change as the story develops, events occur, stages shift and different participants come and go. By depicting such complexities, the paper aims to demonstrate that autobiographical self-translation is a process in which the translator lives his or her life once again while translating the self from one language to another.